Religious-Sociocultural Networks and Social Capital Enhancement in Pesantren - Sutomo, Sutomo; Musnandar, Aries; Alzitawi, Diaya Uddeen Deab Mahmoud; Sutrisno, Sutrisno (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Implementing society empowerment models is crucial for addressing micro-level problems where government services often fall short. Despite evidence that social capital significantly contributes to development and poverty reduction, there remains a gap in understanding specific strategies and outcomes of social capital-based empowerment initiatives. This study aims to fill this gap by investigating the unique learning concept of Pesantren Rakyat Sumberpucung (PRS), which emphasizes low- cost, independent, flexible, and mutual assistance principles. Utilizing framework which includes structural opportunity to meet, know-how of social interaction, sense of belonging, and ethos of mutuality, this study employed qualitative research design. Data were gathered through participant observation, semi-structured interviews with village-level stakeholders, in-depth interviews and focus group discussion. The results indicate that the integrative model known as